(untitled) (Revista Espinhaço, 2020)
this work aims to investigate the trend of live births in the municipality of Mariana aer the Fundão dam burst. We used Data from the National System of Live Births (SINASC) for the municipality of Mariana between 2013 and 2018. We analyzed the absolute numbers of live births in each of the six years, as well as the proportion of live births each year in relation to the total registered in the period (2013-2018). Results show that the number of live births has a negative variation in Mariana between 2015 and 2017.